A Broader “Call to Action”: Returning to Advocacy as a Core Mission of Bioethics - Stevens, Ian; Bortolotto, Claire (Canadian Journal of Bioethics / Revue canadienne de bioéthique, 2026)
Recent political events, such as the Trump administration’s call for the removal of Diversity, Equity, and Inclusion initiatives, continue to undermine the marginal gains that the field of bioethics has sought to make in recent decades. Amidst growing nationalistic, far-right rhetoric worldwide, many bioethicists based in the United States are being pressed to find their footing in a political environment evolving largely in opposition to their personal and professional values. However, there are pockets of bioethicists who have long faced these circumstances, remaining excluded from mainstream bioethical discourse, and whose expertise must be embraced now more than ever. In this commentary, we highlight the central role advocacy has had and should play in bioethics, as demonstrated by the ongoing work of marginalized bioethicists. To effectively return to advocacy as a core mission of bioethics, and to mobilize acts of advocacy against injustices brought about by political tides, we argue that collaborative efforts require whole-heartedly engaging all parties rather than allowing their siloed operation outside the mainstream, privileged, Western, and exclusionary paradigms that have historically dominated the field. If this can be achieved, we believe that bioethics will secure an enduring future irrespective of any governmental adversaries or power structures that it may face.